Effect of anti-corrosive coatings on the performance of high temperature vulcanized silicone rubber insulator - Hongwei Mei; Xiyuan Guan; Chenglong Zhao; Liming Wang; Xiangyun Fu (2017 IEEE Electrical Insulation Conference (EIC), 2017)
With the advantage of low costs and simple construction process, anti-corrosive coatings are widely applied to prevent rusting corrosion of transmission tower caused by sulfide and chloride corrosion in the air. However, Anti-corrosion coatings that fall on the surface of insulators during the maintenance process of electrochemically eroded electrical tower can affect the performance of high temperature vulcanized silicone rubber insulator. The software simulation and experimental research are used to study the effect of the anti-corrosive coating on the properties of high temperature vulcanized silicone rubber insulator. The simulation software was used to analyze electric field on the surface of insulator. Some high temperature vulcanized silicone rubber specimens covered different anti-corrosion coatings were prepared, the hydrophobicity and hydrophobic transfer property and the flashover voltage of these specimens were studied. The results show that anti-corrosive coating will decrease the hydrophobic transfer property and reduce the flashover voltage of high temperature vulcanized silicone rubber specimens.